2017
DOI: 10.1155/2017/6095205
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Role of NEDD9 and P38 Protein Expression Levels in Urinary Bladder Transitional Cell Carcinoma

Abstract: Background. The most common malignant tumor of the urinary bladder is transitional cell carcinoma (TCC). Neural precursor cell-expressed developmentally downregulated protein 9 (NEDD9) is found to be a cell adhesion mediator. P38 Mitogen-Activated Protein Kinase is a serine/threonine kinases member which can mediate carcinogenesis through intracellular signaling. Methods. To assess their prognostic role; NEDD9 and p38 protein were evaluated in sections from 50 paraffin blocks of TCC. Results. The high expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…NEDD9 overexpression was reported in 1309 (52.9%) of the 2476 included patients. Amongst all study cohorts, 3 evaluated lung cancer,23,27,33 4 assessed gastric cancer,28,30,32,39 3 undertook urinary bladder carcinoma,31,34,36 2 illustrated pancreatic carcinoma,29,38 and single studies focused on breast cancer,25 colorectal cancer,24 hepatocellular carcinoma,26 renal carcinoma,37 melanoma,35 and ovarian cancer 8. Studies were conducted in China (11), Japan (1), Turkey (3), Croatia (1), and Egypt (2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NEDD9 overexpression was reported in 1309 (52.9%) of the 2476 included patients. Amongst all study cohorts, 3 evaluated lung cancer,23,27,33 4 assessed gastric cancer,28,30,32,39 3 undertook urinary bladder carcinoma,31,34,36 2 illustrated pancreatic carcinoma,29,38 and single studies focused on breast cancer,25 colorectal cancer,24 hepatocellular carcinoma,26 renal carcinoma,37 melanoma,35 and ovarian cancer 8. Studies were conducted in China (11), Japan (1), Turkey (3), Croatia (1), and Egypt (2).…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies8,2335,38,39 included OS and a follow-up time of 8–125 months. The HR and 95% CI were directly recorded in 11 studies 8,2326,2831,34,35. HR was inferred from the remaining studies using the Tierney method to estimate HR from Kaplan–Meier survival curves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results presented both p38 (SB203580) and ERK inhibitor (PD98059) significantly inhibit NF‐κB activation in TSGH 8301 cells. Harb et al found high expression of p38 as poor prognostic marker was correlated with high grade stage and distant metastasis in bladder cancer. ERK and p38 MAPK activate cell growth and invasive ability in bladder cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…Bladder cancer continues to represent a major health threat, considering the fact that it is one of the major foundations of morbidity and mortality worldwide, accounting for nearly 429,800 new incidence cases and 165,100 deaths per year, it is one of the most common malignant neoplasms in the urological system and is considered as the fourth most prevalent neoplasm in males [1,2]. In Egypt, bladder malignancies are the most common among urinary system malignant tumors (90.71%) and the third among all malignancies [3]. Bladder cancer encompasses a wide spectrum of malignancies; yet its main histological type is urothelial carcinoma, which mostly develops along two main, largely independent but rather overlapping biological pathways, commonly known as papillary and non-papillary tumors.…”
Section: Introductionmentioning
confidence: 99%